Social-ecological justice in cities: a spatial vulnerability approach - Johannes Langemeyer; Svea Busse; Agnieszka Arabas; Giulia Benati; Tomasz Bergier; Sara Maestre-Andrés; Isabel Melo (npj Urban Sustainability)
Abstract Ecological and social injustices are deeply intertwined, yet their integration into strategic spatial planning is widely lacking. This paper presents a spatial, participatory, multi-criteria approach to assess social-ecological vulnerabilities in the Metropolitan Area of Krakow (MK), Poland. Our approach incorporates co-created insights into urban vulnerabilities, considering social and ecological sensitivities alongside exposure to social and environmental hazards. In collaboration with local planning bodies, the co-creation process identified ten critical vulnerabilities, including to river flooding, to noise pollution, and to drought. A comprehensive data analysis with 47 indicators mapped social and ecological vulnerabilities spatially. This detailed assessment establishes a foundation for a strategic spatial planning in MK, suggesting a paradigm shift towards social-ecological needs-based green space planning and addressing spatially explicit social-ecological vulnerabilities under consideration of diverse preferences.